2014
DOI: 10.1038/ncomms6729
|View full text |Cite
|
Sign up to set email alerts
|

An artificial PPR scaffold for programmable RNA recognition

Abstract: Pentatricopeptide repeat (PPR) proteins control diverse aspects of RNA metabolism in eukaryotic cells. Although recent computational and structural studies have provided insights into RNA recognition by PPR proteins, their highly insoluble nature and inconsistencies between predicted and observed modes of RNA binding have restricted our understanding of their biological functions and their use as tools. Here we use a consensus design strategy to create artificial PPR domains that are structurally robust and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
133
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(144 citation statements)
references
References 62 publications
10
133
0
1
Order By: Relevance
“…P-type PPR proteins were shown to participate in various aspects of organellar RNA processing, whereas PLS PPR proteins have been almost exclusively associated with C-to-U RNA editing (for review, see Barkan and Small, 2014;Hammani and Giegé, 2014). Recent crystal structures showed that PPR motifs adopt an antiparallel helixturn-helix fold whose repetition forms a solenoid-like structure (Ringel et al, 2011;Howard et al, 2012;Ban et al, 2013;Yin et al, 2013;Coquille et al, 2014;Gully et al, 2015). PPR tracks organize highly specific interaction domains that were shown to associate with single-stranded RNAs (Schmitz-Linneweber et al, 2005;Beick et al, 2008;Uyttewaal et al, 2008a;WilliamsCarrier et al, 2008;Pfalz et al, 2009;Cai et al, 2011;Hammani et al, 2011;Prikryl et al, 2011;Khrouchtchova et al, 2012;Manavski et al, 2012;Zhelyazkova et al, 2012;Ke et al, 2013;Yin et al, 2013).…”
mentioning
confidence: 99%
“…P-type PPR proteins were shown to participate in various aspects of organellar RNA processing, whereas PLS PPR proteins have been almost exclusively associated with C-to-U RNA editing (for review, see Barkan and Small, 2014;Hammani and Giegé, 2014). Recent crystal structures showed that PPR motifs adopt an antiparallel helixturn-helix fold whose repetition forms a solenoid-like structure (Ringel et al, 2011;Howard et al, 2012;Ban et al, 2013;Yin et al, 2013;Coquille et al, 2014;Gully et al, 2015). PPR tracks organize highly specific interaction domains that were shown to associate with single-stranded RNAs (Schmitz-Linneweber et al, 2005;Beick et al, 2008;Uyttewaal et al, 2008a;WilliamsCarrier et al, 2008;Pfalz et al, 2009;Cai et al, 2011;Hammani et al, 2011;Prikryl et al, 2011;Khrouchtchova et al, 2012;Manavski et al, 2012;Zhelyazkova et al, 2012;Ke et al, 2013;Yin et al, 2013).…”
mentioning
confidence: 99%
“…Ideally one could target unmodified RNA, both for simplicity and to preserve as much native RNA structure and function as possible (4,5). It has been proposed that proteins such as the Caenorhabditis elegans Puf (6), the human PumHD (Pumilio homology domain) (7), or members of the pentatricopeptide family (8) could serve such a purpose. Each of these proteins is made of many similar units, each of which targets one RNA base.…”
mentioning
confidence: 99%
“…The 2nd, 5th, and 35th (or 1st, 4th, and 34th or 3rd, 6th, and 1st in other numbering systems) residues at each repeat are considered to be RNA selection "codes" (9)(10)(11). Based on these codes, several PPR proteins have been successfully modified to recognize predictable RNA targets (9,(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…The 2nd, 5th, and 35th (or 1st, 4th, and 34th or 3rd, 6th, and 1st in other numbering systems) residues at each repeat are considered to be RNA selection "codes" (9-11). Based on these codes, several PPR proteins have been successfully modified to recognize predictable RNA targets (9,(12)(13)(14)(15)(16)(17).The small MutS-related (SMR) domain was originally identified at the C terminus of MutS2 in the cyanobacterium Synechocystis (18). SMR proteins are widely distributed in almost all organisms (19).…”
mentioning
confidence: 99%